Dismal outcome of gastroschisis in a resource-limited country in West Africa: Relevant issues and what to expect? - Cedric Bignon Assouto; Amoussou Sedjro Clotaire Romeo Houegban; Beaudelaire Romulus Assan; Nicole Enianloko Tchiakpe; Michel Armand Fiogbe; Antoine Seraphin Gbenou (EL-Med-Pub, 2022)
Background: Gastroschisis often has a fatal outcome in developing countries. Its outcome is taken as an indicator of the level of healthcare in a particular healthcare facility. The aim was to study the outcome of the management of gastroschisis and to identify the main challenges of its treatment in a country with limited resources. Methods: This is a prospective and descriptive study conducted over a period of 4 years (2016-2020). It included all the neonates admitted to the two referral hospitals of our country with the diagnosis of gastroschisis. Each of the university hospitals had a neonatology unit. Parenteral nutrition and assisted ventilation were not available. Results: Twenty patients were admitted to our hospitals with an annual frequency of five cases. The sex ratio (M:F) was 1.5. Only one of the 20 mothers (5%) of the patients had an antenatal diagnosis and was the only one born in a university hospital. The remaining (19-95%) were referred to a university hospital after their birth. None of the 20 patients had received parenteral nutrition. Surgically, seven babies (35%) had benefited from the placement of a silo with progressive reduction of the bowels. The mortality of gastroschisis was 100% and the average life span of the patients was 4.5 days [1-20 days]. Conclusion: It is important to act appropriately on the whole chain of management of gastroschisis from antenatal diagnosis to treatment so that this pathology is no longer fatal for newborns in countries with limited resources.